Risk matrix construction method based on DIP-IMM-KF algorithm driving - WANG WEI; XU YANG; LIANG HONGCHAO; SUN BAOFENG; CUI YUNLONG; LI CHI; ZHOU HUXING; MA GUODONG (2025)
The invention belongs to the field of traffic control system and automatic driving vehicle track prediction, and particularly relates to a risk matrix construction method based on DIP-IMM-KF algorithm driving, which comprises the following steps: step 1, constructing a risk field considering various factors, wherein the virtual quality, the geometrical shape, the speed, the accelerated speed, the course angle and the equivalent distance of the automatic driving vehicle are considered, and safety potential field influence factors of the vehicle are constructed, and 2, vehicle track intention probability prediction under the dynamic interactive perception interactive multi-model based on a priority order mechanism is carried out; and 3, constructing a risk matrix based on the risk field and the dynamic interactive perception interactive multi-model. By constructing a discrete risk matrix, quantification of the risk matrix is realized in a complex and changeable traffic environment and time-space characteristics